In situ human papillomavirus (HPV) genotyping of cervical intraepithelial neoplasia in South African and British patients: evidence for putative HPV integration in vivo. - Cooper, K (1991)
In South Africa asymptomatic wart virus infection diagnosed by morphological criteria occurs in 16-20% of all ethnic groups; the incidence in black women is 66%. To identify human papillomavirus (HPV) types the prevalence of HPV in cervical intraepithelial neoplasia (CIN) in South African women (n = 72) with age matched British women (n = 73) was compared by non-isotopic in situ hybridisation (NISH) using digoxigenin labelled probes for HPV 6, 11, 16, 18, 31, 33 and 35 on archival biopsy specimens. A higher proportion of British biopsy specimens (68%) contained HPV than those from South Africa (50%) in CIN 2 and 3; this difference was due to HPV 16. Thirty six per cent of the positive biopsy specimens from South African women also contained HPV 33/35 compared with 16% in the United Kingdom. There was no difference in HPV detection with age in either group. These data indicate that HPV types vary geographically, with "minor" HPV types being more common in South Africa. Three qualitatively distinct NISH signals were observed; a diffuse (type 1) signal in superficial cells, mainly koilocytes; a punctate signal (type 2) in basal/"undifferentiated" cells in CIN 3; and combined type 1 and 2 signals in CIN with wart virus infection (type 3). The punctate signal may represent HPV integration.